A Rare Case of Congenital Pericardial Cyst Detected Postmortem - Gün, Berk; Çelik, Cemil; Yeşiltepe, Gözde; Gürlek Olgun, Esra; Tokdemir, Mehmet (The Bulletin of Legal Medicine, 2020)
Congenital pericardial cysts are very rare and often found incidentally in many cases, however they can rarely cause life-threatening symptoms. We aimed to discuss on death the effect of the pericardial cyst and fatty changes in the atrioventricular (AV) node that were detected in the autopsy of a 23-year-old postpartum female.In documents; it was written that the woman who was breastfeeding had been suffering from chest pain for some time. In autopsy; an oval, unilocular, cystic structure with a size of 7.5x7.5x4 cm adjacent to the upper lobe of the left lung, hanging on the outer surface of the pericardium was found. In the histopathological examination; fatty changes were observed in the AV node.In our case, complications that occured after the space-occupying effect of the cyst in the mediastinum, such as arrhythmia, right ventricular outflow tract obstruction, cardiac compression, and changes due to fatty AV node were evaluated.
Keywords: Pericardial Cyst; Postmortem; Sudden Cardiac Death; Fatyy AV node